Odpowiedzi

2009-09-28T17:14:39+02:00
A) (2x-3)(x+7) = 2x do kwadratu -21
b) (4-5y)(1-6y) = 4+30y
c) (0,2-2/5z)(10z+1) = 0,2 - 4z
d) (-1/3w-1/2)(4w+6) = -1cała i 1/3w - 3
e) (3a-5)² = 9 a do kwadratu +25
f) (1/3b+3/7)² = 1/9 b do kwadratu + 9/49
g)(0,2c-0,1)(0,2c+0,1) = 0.04c -0,01
h) 8(1/4x-2)² = 8(1/16x do kwadratu +4) = 1/2xdo kwadratu +4
i) -1/12(4y+3)² = -1/12(16y do kwadratu + 9)= 1 cała i 1/3 - 3/4
j) 0,2(2z-5)(2z+5) = 0,2(4z do kwadratu - 25)= 0,8 do kwadratu -5
k) -(3b-2)²+(1-6b)²=-9b do kwadratu +4 +1-36 b do kwadratu =-45b do kwadratu +5
l) (5c-4)²+(5c-4)(5c+4)= (25c do kwadratu +16) + (25c do kwadratu -16) = 50c do kwadratu